Implications of State Position Dualism on the Financial Settlement of PT Garuda Indonesia (Persero) Tbk. - Indrawati, Yuli (Jurnal Ius Constituendum, 2025)
This study raises the issue of the implications of the dualism of the state's position as a public authority and shareholder in the financial settlement of PT Garuda Indonesia without injuring the intended use of APBN. The financial problems of PT Garuda Indonesia (Persero) Tbk. is already on the verge of requiring immediate action from the state. The focus of this research on the dualism of the state's position has never been discussed in previous research, even though this position is a determining element for the government's actions regarding the Garuda problem.  The position of the state itself as the highest public authority and shareholder limits the state's actions to overcome the problems of PT Garuda Indonesia. This is based on the limitation of the use of the state budget (APBN) as regulated in the Constitution, which is only intended for the prosperity of the people. To answer the research problem, the regulations, the theory of legal entities, the public choice theory, the theory of state responsibility, and the international practices are used as analytical tools. The result of the analysis is that the efforts made by the state, both as a public authority and as a shareholder, must be based on considerations of benefits for the interests of the people – not based on mere nostalgia. Learning from the history of Garuda's management governance which has never improved significantly, the Government should not need to help Garuda because it will only waste the APBN and not be beneficial to the community, because the most important benefit is in deciding on APBN spending actions.  Actions to increase capital can be carried out as long as it is believed that with the addition of capital, PT Garuda Indonesia can bounce back from adversity and generate sufficient profits to provide dividends to the state. If indeed the condition of PT Garuda Indonesia it is not possible to get up and operate so as to generate dividends, preferably PT Garuda Indonesia bankrupt.